1965
DOI: 10.1017/s0021859600048863
|View full text |Cite
|
Sign up to set email alerts
|

A field study of coat shedding in cattle under conditions of equal day-length but different temperatures

Abstract: A comparison has been made over 2 years of spring shedding in cattle maintained in two environments experiencing a similar photoperiod but vastly different seasonal temperatures. At each location (Walcha and Narrabi, N.S.W.) experimental animals were divided into two nutritional groups, namely a Feed group and a Pasture group.2. In 1961-62 both the Feed and Pasture groups in the warmer climate of Narrabri shed their winter coats in October, while animals maintained under the cooler conditions of Walcha did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…We found later moult at higher latitudes in contrast to findings in muskoxen where earlier shedding occurred in animals at 69 degrees N than at 57 degrees N (Wilkinson, 1974). Whereas photoperiod is considered to be a primary cue for moult (Lincoln and Ebling, 1985;Zimova et al, 2018), temperature also plays a role; for example, cattle populations at the same latitude but different temperatures show earlier moult where lower and warmer (Murray, 1965). In northern mountain goats, delayed moult may be warranted if a warm coat is still needed for the late spring cold.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…We found later moult at higher latitudes in contrast to findings in muskoxen where earlier shedding occurred in animals at 69 degrees N than at 57 degrees N (Wilkinson, 1974). Whereas photoperiod is considered to be a primary cue for moult (Lincoln and Ebling, 1985;Zimova et al, 2018), temperature also plays a role; for example, cattle populations at the same latitude but different temperatures show earlier moult where lower and warmer (Murray, 1965). In northern mountain goats, delayed moult may be warranted if a warm coat is still needed for the late spring cold.…”
Section: Discussioncontrasting
confidence: 86%
“…Most mammals moult to replace worn out hairs and provide different summer and winter coats (Ryder, 1965), including moose (Alces alces ), bison, elk (Cervus canadensis ), and thinhorn sheep (Ovis dalli ). While moult is a relatively understudied life history event (Beltran et al, 2018), it is well-established that photoperiod and, to a lesser extent temperature, control moult onset (Murray, 1965;Lincoln and Ebling, 1985;Mo et al, 2006;Zimova et al, 2018). Moult is known to occur latest in lactating mountain goat females (Déry et al, 2019) likely because, as documented in red deer (Cervus elaphus ), the costs of milk production affect female body condition even though food may be most abundant in summer (Clutton-Brock et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high visibility of massive chunks of hair hanging from species like bison ( Bison bison ) and muskoxen ( Ovibos moschatus ) (Berger & Cunningham, 1994; Wilkinson, 1974), for most species little is known about the phenology of shedding, or the extent to which it varies across broad latitudinal or altitudinal gradients (Beltran et al., 2018). Nonetheless, it is well established that photoperiod and, to a lesser extent, temperature control molt phenology (Lincoln & Ebling, 1985; Mo et al., 2006; Murray, 1965; Zimova et al., 2018). The timing and rate of molt may also be influenced by body condition, which depends on resource availability and reproductive output.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in cattle has established roles for temperature and day length in initiating seasonal coat shedding [9,66]. To our knowledge, the effect of their interaction has never been explicitly examined.…”
Section: The Effects Of Temperature and Photoperiodmentioning
confidence: 99%
“…Among ungulates and other mammals, the effects of temperature and day length interact to induce seasonal molting. This interaction has never been explicitly demonstrated in cattle, although Yeates (1955) [9] showed that artificial manipulation of day length can be used to perturb the timing of hair coat shedding regardless of temperature, while Murray (1965) [66] found a moderate effect of temperature on hair coat shedding among cattle at similar latitudes.…”
Section: Introductionmentioning
confidence: 99%